Improving students' performance in geometry: an empirical evidence of the effectiveness of brainstorming learning strategy - Kazaik Benjamin Danlami; Yusuf Feyisara Zakariya; Yusuf Feyisara Zakariya; Bashir Balarabe; Sarah Bader Alotaibi; Tahani Mohammed Alrosaa (Frontiers in Psychology, 2025)
BackgroundThe persistent challenges in geometry performance among secondary school students in Nigeria demand innovative teaching methods that extend beyond conventional strategies.ObjectiveThis pretest and post-test quasi-experimental study investigated the effectiveness of brainstorming as an instructional approach to improve students' geometry performance.MethodsThe research involved 140 students from two coeducational public secondary schools, with 73 students assigned to an experimental group taught using the brainstorming strategy. In comparison, 67 students were placed in a control group that received instruction through the conventional method. Data were collected using the Geometry Performance Test (GPT) with a reliability coefficient of 0.83 obtained using the test-retest method. The data generated were analyzed using descriptive and inferential statistics to address the research questions and test the study's hypotheses.ResultsThe results indicated that the experimental group significantly outperformed the control group in posttest scores, F(1, 137) = 227.124, p < 0.001, with a mean score of 66.99 (SD = 9.17) compared to 46.76 (SD = 6.18) in the control group. No significant gender difference was observed in performance gains, F(1, 34) = 1.609, p = 0.213, suggesting that brainstorming is an effective teaching strategy without gender bias.ConclusionThese findings show the potential of brainstorming as a powerful tool for improving students' performance in geometry with equitable effectiveness among male and female secondary students. Thus, we recommended that educators should integrate brainstorming into their mathematics classrooms as a proxy to close performance gaps among male and female students in mathematics and improve students' performance in mathematics. As this study was conducted in two public secondary schools in Kaduna State, Nigeria, we acknowledge that the findings are context-specific and may not be generalizable without caution.